The existential subjectivity in the short stories of Ferit Edgü and Demir Özlü - İş, Ayşe Öykü. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2007., 2007)
This study examines the reflections of existentialism, which has its roots in Western philosophy and literature, in Ferit Edgü and Demir Özlü’s early stories. The study takes Ferit Edgü’s collection of stories entitled Kaçkınlar and Bozgun and Demir Özlü’s Bunaltı, Soluma and Boğuntulu Sokaklar as primary sources. In addition to these works, in order to understand the authors’ conception of existentialism, I have made use of the authors’ texts published in several periodicals. The study conducts the textual analysis through the theoretical framework and the main concepts of existentialism. The main effort of this study is to see how Edgü and Özlü conceptualized and fictionalized the concepts of existentialism in their early stories. To this end, I have first tried to explain the rise of existentialism in the West and the main path existentialism took. In this context it can be said that existentialism emphasizes freedom and responsibility along with meaninglessness, lack of faith, despair and nuisance. Edgü and Özlü have transformed the existentialist concepts according to their own perceptions shaped by the social and literary conditions of Turkey in 1950s. In the stories of Edgü and Özlü, rather than a subjectivity that is under a constant change, a subjectivity where expansion and existential possibilities are restricted is at issue.
Keywords: Existentialism in literature.